Work and family: The perception of balance among female teachers in Northern Malaysia - Aziz, Azelin; Chang, Artemis (Universiti Utara Malaysia, 2013)
Women’s participation in paid employment has become a common scenario even in non-western developing countries.For example in Malaysia, the trend is growing although the traditional gender role remains strong in Malaysian society.Even though working, women are still expected to assume major responsibilities at home.Thus, as opposed to men, women in this society face the challenge to satisfactorily balance work and family.This study was carried out to explore how Malaysian women perceive the meaning of a balanced work-family life.Sampling women teachers, the interview findings revealed that work-family balance was mainly perceived in terms of an individual’s ‘ability to fulfill role obligation’ appropriately in both the work and family domains. A few participants also viewed balance in the context of role satisfaction and role interference.Overall, the results support the assumption in the literature that perceptions of work-family experience are not universal, rather, the construct of work-family balance is culture-specific.